Optimality and duality for variational problems with generalized convexity - Mukherjee R.N.; Rao Ch.P. (My University, 2025)
The concept of type I convexity conditions has been extended to the continuous case and has been used to study optimality and duality results for a class of variational problems. The results have also been extended to fractional prrogramming problems, in the last section of the paper.